2020
DOI: 10.2147/cmar.s280780
|View full text |Cite
|
Sign up to set email alerts
|

<p>Differential Impact of Systemic Lymphadenectomy Upon the Survival of Patients with Type I vs Type II Endometrial Cancer: A Retrospective Observational Cohort Study</p>

Abstract: Purpose: To determine whether systemic lymphadenectomy exerts a similar effect on the survival of patients with either type I or type II endometrial cancer (EC). Patients and Methods: In this retrospective study, 682 eligible patients diagnosed with EC were typed according to the pathological reports. The thoroughness of lymphadenectomy was evaluated by the lymph node number of which the cutoff value was determined by the receiver operator characteristic (ROC) curve and Youden index. The impact of thoroughness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
3
1
0
Order By: Relevance
“…Xu et al evaluated, retrospectively, the effect of lymphadenectomy on survival rates in patients with (type I and type II) endometrial cancer. The authors aimed to determine the number of lymph nodes to be resected in order to achieve an overall survival bene t, and found no threshold for endometrioid endometrial carcinoma [30]. This is in line with our data, which indicated that systematic lymphadenectomy does not improve overall survival rates.…”
Section: Discussionsupporting
confidence: 83%
“…Xu et al evaluated, retrospectively, the effect of lymphadenectomy on survival rates in patients with (type I and type II) endometrial cancer. The authors aimed to determine the number of lymph nodes to be resected in order to achieve an overall survival bene t, and found no threshold for endometrioid endometrial carcinoma [30]. This is in line with our data, which indicated that systematic lymphadenectomy does not improve overall survival rates.…”
Section: Discussionsupporting
confidence: 83%
“…Scientifically, the impact of the extend of lymphadenectomy remains unclear. Recently, Xu et al reported no influence of the total number of resected lymph nodes on patient's survival, while other authors retrospectively pointed out a cutoff of > 10 nodes for a better survival [24,25]. The present study confirmed that patients with lymphadenectomy develop lymphatic complications significantly more often than those without lymphadenectomy (p < 0.01).…”
Section: Discussionsupporting
confidence: 80%
“…Xu et al evaluated, retrospectively, the effect of lymphadenectomy on survival rates in patients with (type I and type II) endometrial cancer. The authors aimed to determine the number of lymph nodes to be resected in order to achieve an overall survival benefit, and found no threshold for endometrioid endometrial carcinoma [24]. This is in line with our and the previously presented data, which indicate that the systematic lymphadenectomy does not improve overall survival rates.…”
Section: Discussionsupporting
confidence: 77%
“…Large retrospective studies have shown that lymphadenectomy is associated with longer overall survival, especially in high-risk endometrial cancer ( 63 ). Moreover, concerning type II endometrial cancer, one large retrospective study ( 64 ) showed that when >20 lymph nodes where removed there was an overall survival benefit and another retrospective study ( 65 ) demonstrated that systemic pelvic and paraaortic lymphadenectomy is a significant independent therapeutic factor that prolongs disease-free and overall survival. However, two large randomized control trials showed no statistically difference in disease-free and overall survival between lymphadenectomy or not ( 66 , 67 ).…”
Section: Lymph Nose Assessmentmentioning
confidence: 99%